Microstructural banding of directed energy deposition-additively manufactured 316L stainless steel. (10th April 2021) - Hwa, Yoon; Kumai, Christopher S.; Devine, Thomas M.; Yang, Nancy; Yee, Joshua K.; Hardwick, Ryan; Burgmann, Kai
Abstract: The microstructures of 316 L stainless steel created by rapid solidification are investigated by comparing the similar microstructures of individual hatches of directed energy deposition additive manufacturing (DED-AM) and those of single, laser surface-melted tracks formed on a solid plate. High recoil pressure, which is exponentially dependent on the laser beam power density, induces convection of the melt pool, which causes formation of microstructural bands in the as-solidified microstructure. The microstructural bands are associated with changes in the chromium concentration and are a significant component of the inhomogeneous microstructure of DED-AM.